Challenges in Teaching the English Tense System to Non-Native Learners (Journal of Science-Innovative Research in Uzbekistan, 2025)
The English tense system is one of the most complex aspects of the language, presenting significant challenges for non-native learners. Its intricate structure, encompassing various tenses, aspects, and uses, often leads to confusion and errors. These difficulties are further compounded by learners' native language interference, differences in grammatical frameworks, and the abstract nature of certain tenses. Understanding and addressing these challenges is crucial for effective English language teaching, as mastery of tenses is essential for accurate communication in both spoken and written contexts. This study explores the key obstacles faced by non-native learners and suggests strategies for overcoming them. This article explores the difficulties faced by learners in mastering the tense system and discusses effective strategies to overcome these challenges